The Influence of Social Media Marketing Activities Instagram on The Purchase Intention of Ultra Milk Products - Vania Amelia; Riski Taufik Hidayah (Publikasi Indonesia, 2024)
Packaged beverages, including liquid milk, are widely favored among Indonesians for their convenience and accessibility, with Ultra Milk being a notable brand. Despite a sales surge in the third quarter of 2023, Ultra Milk's standing in the Top Brand Award has declined over the past two years. To explore this trend, the author examines the impact of Instagram's Social Media Marketing Activities (SMMA) on Ultra Milk's purchase intention. This quantitative study employs structural equation modeling (SEM-PLS) analysis using SmartPLS 4.0, with 100 respondents chosen through purposive sampling based on specific criteria. Questionnaires were distributed via Google Forms. The findings reveal a positive association between SMMA and brand equity. Moreover, brand equity positively influences electronic word-of-mouth (e-WOM), which subsequently affects customer purchase intention. Additionally, SMMA has a direct impact on customers' purchase intentions. These insights shed light on the role of social media marketing in shaping consumer behavior towards Ultra Milk.